Influence of the Nature and Structure of Polyelectrolyte Cryogels on the Polymerization of (3,4-Ethylenedioxythiophene) and Spectroscopic Characterization of the Composites - Svetlana Laishevkina; Natalia Shevchenko; Olga Iakobson; Anatoly Dobrodumov; Vladimir Chelibanov; Elena Tomšík (Molecules, 2022)
Conductive hydrogels are polymeric materials that are promising for bioelectronic applications. In the present study, a complex based on sulfonic cryogels and poly(3,4-ethylenedioxythiophene) (PEDOT) was investigated as an example of a conductive hydrogel. Preparation of polyacrylate cryogels of various morphologies was carried out by cryotropic gelation of 3-sulfopropyl methacrylate and sulfobetaine methacrylate in the presence of functional comonomers (2-hydroxyethyl methacrylate and vinyl acetate). Polymerization of 3,4-ethylenedioxythiophene in the presence of several of the above cryogels occurred throughout the entire volume of each polyelectrolyte cryogel because of its porous structure. Structural features of cryogel@PEDOT complexes in relation to their electrochemical properties were investigated. It was shown that poly(3,4-ethylenedioxythiophene) of a linear conformation was formed in the presence of a cryogel based on sulfobetaine methacrylate, while minimum values of charge-transfer resistance were observed in those complexes, and electrochemical properties of the complexes did not depend on diffusion processes.